Rancang Bangun Aplikasi Penjualan Air Mineral Pada Toko Tirta Arlita Gresik - Andriyanti, Emma Mery; Sulistiowati, sulistiowati; Soebijono, Tony (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Tirta Arlita Gresik is a store that specializes in the sale of water mineral.system selling used today is the conventional system , the buyer must Dating directly to the store to see the over product .so, has several problems including: frequent errors , repetition of the input data which still form the book keeping , and the delay in making the report .To solve the problem, in the storage and recording of sales transactions need to be a computerized data . To meet these needs , the final project is made of applications mineral water sales in Tirta Arlita Gresik . Keywords : Application , cash sales , sales returns , procurement , Tirta Arlita Gresik Store